Effects of scattering on ultrasound wave transmission through bioinspired scaffolds. (February 2022) - Fielder, Marco; Nair, Arun K.
Abstract: Enhancing tissue growth in scaffolds using ultrasound waves while maintaining the structural integrity of the scaffolds is a challenging problem. Previous studies have primarily focused on the effect of ultrasound waves directly on the tissue, but how the ultrasound wave interacts with the scaffold needs to be further understood, which will have a significant effect on the response of tissue to mechanical stimulation. In this study we investigate how ultrasound wave transmission differs between scaffolds with uniform pore shapes (triangle, square, rectangle, hexagon) and a bioinspired scaffold with higher structural integrity that is inspired from the atomic structure of hydroxyapatite which is a primary component of bone. We use finite element method and ultrasound experiments on 3D-printed scaffolds composed of Acrylonitrile butadiene styrene (ABS) with constant porosity to predict the effect of pore shape and wave signal frequency in the range of 1–20 MHz on acoustic wave scattering and transmission. We find that the pore shape of the scaffold affects the magnitude of ultrasound transmission even when porosity is constant, and that the bioinspired scaffolds can allow as much as 67% more wave transmission compared to scaffolds with rectangular or square pore shapes at 1 MHz frequency. Triangular and hexagonal pores are also found to produce more nonuniform transmitted wavefronts compared to the square and rectangular pores. Peak density is defined as the number of local extrema of the transmitted wave frequency power spectrum and measures the uniformity of the transmitted wave. We find that a higher peak density value for the bioinspired scaffold due to its nonsymmetric structure further produces more nonuniform wave scattering. The results of this study are important for designing bioinspired tissue scaffold geometries to control ultrasound wave penetration and to enhance mechanical stimulation for tissue growth and will also aid in the ultrasonic characterization of porous structures based on changes in pore geometry.